Kinerja Ekspor Produk Teh Indonesia di Pasar Internasional: Asesmen Perjanjian Perdagangan Indonesia - Putro, Fikri Aldi Dwi; Widyastutik; Hidayat, Nia Kurniawati (National Research and Innovation Agency, 2024)
The decline in Indonesian tea products export performance does not correspond to the Government initiatives to reduce barriers through trade agreements. This research aims to analyse the export performance and the role of trade agreements towards Indonesian tea products export. This study employs panel data regression with a 15-year time series (2007-2021) and a cross-section of 40 destination countries. The data are analysed using a modified export approach gravity model with Poisson Pseudo-Maximum Likelihood (PPML) estimation. The research results show that the Indonesian tea products export destinations are dominated by Asia (19 countries) and Europe (12 countries). The regression results suggest that the implementation of trade agreements with Asian and European region countries has not effectively increased Indonesian tea products export. On the other hand, the implementation of trade agreements with other region countries, i.e., Australia and New Zealand, has successfully promoted export towards Indonesian tea products. Those can be attributed to trade agreements underutilization and trade barriers imposed by the trade agreement members. Hence, inward and outward-looking strategies are necessary to promote the export creation effect of implemented trade agreements towards Indonesian tea product exports.